Characteristics and outcomes of older persons attending the emergency department: a retrospective cohort study. - O'Neill, Desmond; Romero-Ortuno, Roman; Coughlan, Tara; Kennelly, Sean (My University, 2014)
Background: The analysis of routinely collected hospital data informs the design of specialist services for at-risk older people. Aim: Describe the outcomes of a cohort of older emergency department (ED) attendees and identify predictors of these outcomes. Design: retrospective cohort study. Methods: All patients aged 65 years or older attending an urban university hospital ED in January 2012 were included (N = 550). Outcomes were retrospectively followed for 12 months. Statistical analyses were based on multivariate binary logistic regression models and classification trees. Results: Of N = 550, 40.5% spent ≤6 h in the ED, but the proportion was 22.4% among those older than 81 years and not presenting with musculoskeletal problems/fractures. N = 349 (63.5%) were admitted from the ED. A significant multivariate predictor of in-hospital mortality was Charlson comorbidity index [CCI; odds ratio = 1.19, 95% confidence interval: 1.07, 1.34, P = 0.002]. Among patients who were discharged from ED without admission or after their first in-patient admission (N = 499), 232 (46.5%) re-attended ED within 1 year, with CCI being the best predictor of re-attendance (CCI ≤ 4: 25.8%, CCI > 5: 60.4%). Among N = 499, 34 (6.8%) had died after 1 year of initial ED presentation. The subgroup (N = 114) with the highest mortality (17.5%) was composed by those aged >77 years and brought in by ambulance on initial presentation. Conclusions: Advanced age and comorbidity are important drivers of outcomes among older ED attendees. There is a need to embed specialist geriatric services within frontline services to make them more gerontologically attuned. Our results predate the opening of an acute medical unit with specialist geriatric input.
PUBLISHED
Keywords: emergency department (ED) attendees; Ageing; Age related diseases